From Sophia to general artificial intelligence: anthropomorphism and consciousness at the current state of art of technology (Revista Direitos Humanos e Democracia, 2024)
The main goal of this article is to define the possibilities and obstacles of the development of an artificial intelligence (AI) capable of being as intelligent and capable as (or even more than) the human being. As a result, it was found that despite the great scientific advances in human behavior and the functioning of the brain, little is known about what consciousness is and how it works, which obliterates the development of a general artificial intelligence (GAI). Methodologically, it is a research developed according to the dialectical method of procedure, with a qualitative and transdisciplinary approach, and bibliographic review research technique.
Keywords: artificial intelligence; consciousness; anthropomorphism